Educational Management of Special Sports Classes: An Integration of Religious Knowledge and Physical Education at NU Al Ma’ruf Senior High School, Kudus - Miftah Miftah; Islah Gusmian; Fitri Wulandari (Journal of Science and Education (JSE), 2025)
This article aims to strengthen the discourse on integrated curriculum systems within Islamic education. The integration system in question incorporates physical education into the well-established pesantren (Islamic boarding school) framework. As a result of this integration, a Special Sports Class referred to as Kelas Khusus Olahraga (KKO) has emerged. KKO represents an innovative breakthrough initiated by NU Al Ma’ruf Senior High School in Kudus to provide education that aligns with contemporary needs, addressing the era's demands while accommodating students' interests and talents. KKO serves as an alternative response to the current challenges faced by Islamic educational institutions. Employing a library research method, this study explores how NU Al Ma’ruf Senior High School has developed an integrated curriculum model that aligns with Islamic teachings, embraces modern developments, and preserves cultural heritage. The integration model presented in this study constitutes a form of renewal in Islamic education, illustrating how institutions traditionally perceived as conservative are undergoing significant transformation to meet present-day educational needs. The aim of this study is to explore an integrated management model between Islamic religious education and physical education within the Special Sports Class.